Approaches to the increasing linguistic diversity in Greek and Polish classrooms: Different contexts with similar problems - Papasoulioti, Aspasia; Fountana, Maria; Szczepaniak-Kozak, Anna; Adamczak-Krysztofowicz, Sylwia (Glottodidactica, 2023)
The paper discusses key educational issues related to the processes of decision-making and continuous teacher development at the level of the national (educational) authorities in Greece and Poland, regarding the urgency of the needs arising from the intensifying migration in the EU over the last two decades, and in view of the research conducted within the MaMLiSE project. The paper begins by reporting the official decisions and policies which laid the grounds for tackling the considerable linguistic variety that now characterises the school populations in each country, caused by the phenomenon of migration, and with refugee flows included. In addition, country-specific methods and resources used to produce educational materials for pupils from a migration background are presented. Finally, the available educational materials and their suitability to the specificity of each country’s current educational conditions are discussed. The concluding remarks are that a strong need is currently emerging for 1) nominating key-points in the pre- and in-service training of teachers with regard to multilingual classroom management, intercultural awareness and language sensitive subject teaching, 2) extrapolating common features necessary for the production of educational material (e.g. adaptability to new conditions, ease and flexibility of use in class, allowing translanguaging practices), and 3) negotiating shared educational principles (e.g. assessment framework, constructive use of language heritages at schools).